2022
DOI: 10.21608/ajccr.2022.223049
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interest and Inflation Rates on Deposits Behavior of Banks: The Case of Egypt

Abstract: This paper examines the impact of interest and inflation rates on deposits' behavior of banks and investigates the factors influencing the impact of interest and inflation rates movements on deposits' behaviors of banks in Egypt within the period 2000-2018. Using secondary data for the quarterly time series collected from the Statistical Bulletins published by the Egyptian Central Bank. The ARDL methodology and ARCH & GARCH models are used. The results indicate that the volatility of interest rate is not assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Deposit is one of the major shares of bank financial portfolios (Youssef et al, 2022). Financial institutions face challenges especially when there is a structural change in the bank portfolio.…”
Section: Deposit Interest Rate and Inflationmentioning
confidence: 99%
“…Deposit is one of the major shares of bank financial portfolios (Youssef et al, 2022). Financial institutions face challenges especially when there is a structural change in the bank portfolio.…”
Section: Deposit Interest Rate and Inflationmentioning
confidence: 99%
“…Dewi and Haryanto (2015) found that inflation rate, Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) have significant effect on Time Deposit Interest Rate of the Commercial Bank in Indonesia. Research about the impact of interest and inflation rates on deposits' behavior of banks in Egypt conducted by Mohamed Youssef et. al.…”
Section: Introductionmentioning
confidence: 99%